2016
DOI: 10.1021/acs.iecr.6b03990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cu–Zn/Core–Shell Al-MCM-41 as a Catalyst for Reduction of NO: Effect of Zn Promoter

Abstract: A combination of three methodssubstitution, ionexchange, and impregnationwas used to prepare the Cu−Zn/core− shell Al-MCM-41 catalyst with various copper species. The roles of each preparation method and of Zn promoter in the nature of copper were studied by means of in situ Fourier transform infrared spectroscopy of CO and NO adsorption, diffuse reflectance ultraviolet−visible−nearinfrared spectroscopy, X-ray photoelectron spectroscopy, and H 2 temperature-programmed reduction. The results suggested that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 84 publications
(260 reference statements)
4
10
0
Order By: Relevance
“…18 The presence of both external surface CuO and nanosized CuO crystals in the Cu-containing catalysts was also found in the previous works. 18,19…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…18 The presence of both external surface CuO and nanosized CuO crystals in the Cu-containing catalysts was also found in the previous works. 18,19…”
Section: Resultssupporting
confidence: 72%
“…20 During the catalyst preparation, some part of the copper precursor (i.e., Cu(NO 3 ) 2 ) was confined by the capillary effect inside the channels of the catalyst, resulting in the formation of small crystalline CuO species in pores. 18 The presence of both external surface CuO and nanosized CuO crystals in the Cu-containing catalysts was also found in the previous works. 18,19 Generally, Cu 2+ ions at the exchange sites are reduced to Cu 0 via a two-step reduction process.…”
Section: Acs Omegasupporting
confidence: 72%
See 2 more Smart Citations
“…The survey spectrum and high‐resolution XPS of ZnO−Cu(OH)Cl/MCM‐41 showed the existence of Zn, Cu and O (Figure ). The high‐resolution XPS spectra of Zn 2p reveals the binding energies of Zn 2p 3/2 at about 1020.5 eV and Zn 2p 1/2 center at 1043.7 eV, peak shape and peak separation which is ∼23 eV revealed that presence of Zn +2 in ZnO as shown in Figure A. XPS spectra of Cu 2p showed the two peaks centered at 933 eV and 953 eV were assign to Cu 2p 3/2 and Cu 2p 1/2 present in Cu(OH)Cl in where Cu is in +2 oxidation state shown in Figure B .…”
Section: Resultsmentioning
confidence: 99%